INTEGRATING DESIGN THINKING, BUSINESS MODEL CANVAS, AND THEORY OF PLANNED BEHAVIOR TO ENHANCE NON-FORMAL EDUCATION POLICY ACCEPTANCE - Doddi Trisna Nugraha (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Non-formal education expands learning opportunities, yet policy acceptanceremains a challenge due to low stakeholder involvement, unclear structure, andimplementation barriers. This study integrates Design Thinking, BusinessModel Canvas (BMC), and Theory of Planned Behavior (TPB) to enhancepolicy acceptance. Design Thinking fosters stakeholder engagement, BMCstructures policies for clarity, and TPB assesses behavioral factors influencingacceptance. Using a qualitative and participatory approach, data from focusgroups, interviews, and surveys reveal that this integration improves policyinclusivity, transparency, and feasibility. Findings indicate that stakeholderdriven policies are more accepted and easier to implement, aligning with SDGsNo. 4: Quality Education for All. This framework provides a practical guide fordesigning more effective non-formal education policies.